Self-efficacy and psychological well-being among first year nursing students: A cross-sectional study - Wulida Litaqia; Ainun Najib Febrya Rahman; Fadma Aji Pramudita; Sri Yulian Hunowu; Ryan Nuari Pratama (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: The transition to higher education increases first-year nursing students' risk of psychological vulnerability. Self-efficacy has been identified as a potential protective factor; however, evidence focusing on early-stage nursing students remains limited. This study aimed to examine the association and predictive role of general self-efficacy on psychological well-being among first-year nursing students. Research Methodology: An analytical cross-sectional study was conducted among 119 first-year nursing students at a public university in Indonesia using convenience sampling. Data were collected through an online survey using the General Self-Efficacy Scale (GSES) and the WHO-5 Well-Being Index. Descriptive statistics, independent-samples t-tests, Pearson correlation, and linear regression analyses were performed using SPSS with α = 0.05. Results: Self-efficacy demonstrated a moderate positive correlation with psychological well-being (r = 0.42; 95% CI: 0.26–0.56; p < 0.001). Linear regression analysis showed that self-efficacy significantly predicted psychological well-being (β = 0.42; p < 0.001), explaining 18% of the variance (R² = 0.18). No significant gender differences were identified. Conclusion: Self-efficacy is a significant psychological determinant of well-being among first-year nursing students. Early educational interventions aimed at strengthening self-efficacy may enhance students’ mental well-being and academic adjustment